Pengukuran Tingkat Efisiensi Teknis Penjualan Produk Herbal di PT X Menggunakan Metode Data Envelopment Analysis (DEA) - Pratiwi, Gusti Ayu Chintya Artania; Sadiyah, Fitria Naimatu; Rahayu, Novia Aristi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the technical efficiency of herbal product sales at PT X, Sleman branch, with a focus on determining the most efficient input and output variables. The research adopts a descriptive quantitative approach, utilizing the Data Envelopment Analysis (DEA) method to measure efficiency. Several input variables are assessed, including the number of active employees, basic salary, allowances, and bonuses, while the output variable considered is the total amount of herbal product sales. The results, obtained through efficiency measurement using the WinDEAP software, reveal that 50% of the Decision-Making Units (DMUs) are inefficient. Specifically, DMU 1, DMU 3, DMU 4, DMU 5, and DMU 6 fail to achieve optimal efficiency levels. To address this, recommendations for improvement are provided by referring to the efficient DMUs. These recommendations involve tailored input and output adjustments aimed at optimizing sales. Efficiency can be realized if each employee earns a salary of Rp 4,109,733.00 while achieving a minimum sales target of 146 herbal products. Following these recommendations, an assessment of employee performance is conducted. The findings indicate that 30% of marketing employees demonstrate efficient sales performance, whereas 70% still struggle to reach efficiency targets, necessitating further adjustments.